2020
DOI: 10.3389/fcell.2020.608388
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Autophagy in Osteoarthritis

Abstract: Chondrocytes are the only cell type in normal cartilage. The pathological changes of osteoarthritis (OA) mostly revolve around the apoptosis and dysfunction of chondrocytes. Autophagy, as an intracellular degradation system that maintains the steady state of energy metabolism in cells, has been shown to restore the function of damaged chondrocytes, alleviating the occurrence and progression of OA. In this review, we explored the relationship between autophagy and OA and the key molecules of autophagy pathway t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
94
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 95 publications
2
94
1
Order By: Relevance
“…It maintains organelle and protein functions and attenuates the detrimental stress during cell apoptosis (Choi et al, 2013). Existing evidence has suggested that autophagy is suppressed in OA (Shapiro et al, 2014;Zhang et al, 2015) and recovers the function of injured chondrocytes (Duan et al, 2020). According to our screening work, integrin β4 (ITGB4) was identified as a differentially expressed gene (DEG) in OA and is related to autophagy.…”
Section: Introductionmentioning
confidence: 94%
“…It maintains organelle and protein functions and attenuates the detrimental stress during cell apoptosis (Choi et al, 2013). Existing evidence has suggested that autophagy is suppressed in OA (Shapiro et al, 2014;Zhang et al, 2015) and recovers the function of injured chondrocytes (Duan et al, 2020). According to our screening work, integrin β4 (ITGB4) was identified as a differentially expressed gene (DEG) in OA and is related to autophagy.…”
Section: Introductionmentioning
confidence: 94%
“…Usually, a mechanical load or inflammatory cytokines are applied to cells in order to mimic OA conditions. In particular, OA mimic conditions are applied to cells growing in a monolayer, in a scaffold or in a co-culture system [ 62 ]. The use of 3D cell models may represent a good alternative to 2D cultures.…”
Section: In Vitro and In Vivo Models For Oa Studiesmentioning
confidence: 99%
“…Osteoarthritis (OA) is a common degenerative disorder of the joints that accounts for major physical pain in older adults [ 1 , 2 ]. OA could result in severe joint pain, stiffness, limited motion, disability, and in serious cases, the loss of joint mobility [ 3 , 4 ]. OA is regarded as the leading cause of lower limb disability, with a disability rate of up to 53% [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%